PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN IPA DIKELAS IX SMP NEGERI 1 PAGAR ALAM - Yulisa Andriani; Alexon Alexon (DIADIK, 2021)
This study aims to produce interactive multimedia for dynamic electric learning that is feasible and practical and is able to improve student learning achievement. This research method uses development research using modifications and a combination of the Akker development model and Tessmer's formative evaluation. This research goes through the analysis, design and evaluation stages. The interactive multimedia developed was further validated by media experts and material experts. The feasibility of the material got a score of 3.56 in the very feasible category and the feasibility of the media got a score of 3.65 in the very feasible category. To test the practicality of interactive multimedia, it was tested one to one and a small group. The results of the quantitative questionnaire assessment of students had a mean of 3.46 with the very practical category. To test its effectiveness on student’s learning achievement, a field test was carried out. Based on the results of t-test analysis on the pre-test value in the control class and experimental class, the Sig (2 tailed) value was 0.943> 0.05. This means there is no significant difference in the pre-test scores of the control class and the experimental class. Furthermore, based on the results of the t test analysis on the post-test scores of the control class and the experimental class, the Sig (2 tailed) value of 0.001 <0.05 was obtained. This shows a significant difference in the post-test scores of the control class and the experimental class. Based on these results it can be concluded that interactive multimedia is feasible, practical and can improve learning achievement in students